Aortic cannula orientation and flow impacts embolic trajectories: computational cardiopulmonary bypass. (July 2020) - Ho, Raymond; McDonald, Charles; Pauls, Jo P; Li, Zhiyong
Introduction: Emboli events are associated with the aortic cannula insertion and final position in the ascending aorta. However, the impact of subtle changes in aortic cannula movement and flow influencing embolic transport throughout the aortic arch is not well understood. The present study evaluated the aortic cannula's outflow and orientation effect on emboli entering the aortic branch arteries. Methods: A simplified aortic computational model was anteriorly cannulated in the distal ascending aorta with a 21-French straight aortic cannula, and two orientations were analysed by injecting gaseous and solid emboli at pump flows 2, 3 and 5 L/minute. The first aortic cannula orientation (forward flow cannula) was directed towards the lesser curvature. The second aortic cannula orientation (rear flow cannula) was tilted slightly backwards by 15°, providing flow in the retrograde direction. Results: Forward flow cannula produced a primary arch flow, whereas rear flow cannula produced a secondary arch flow resulting in four times longer emboli arch resident times than forward flow cannula. The rear flow cannula had the highest percentage of gaseous emboli entering the brachiocephalic artery of 8%, 12% and 36% (at 2, 3 and 5 L/minute, respectively). Rear flow cannula provided a positive aortic branch arterial flow at all pump flows, whereas at forward flow cannula, the brachiocephalic artery experienced retrograde flows of −1.0% (3 L/minute) and −4.0% (5 L/minute), with the left common carotid −0.23% (5 L/minute). No significant number of solid emboli entered the aortic branch arteries. Conclusion: This numerical study illustrated distinct trajectory behaviours between gaseous and solid emboli where slight changes in aortic cannula orientation influenced idealised emboli direction with higher pump flows magnifying the effects.